2010
DOI: 10.4248/ijos10015
|View full text |Cite
|
Sign up to set email alerts
|

Multilineage Differentiation of Dental Pulp Stem Cells from Green Fluorescent Protein Transgenic Mice

Abstract: Aim The aim of this study was to confirm the multilineage differentiation ability of dental pulp stem cells (DPSCs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 21 publications
2
24
0
1
Order By: Relevance
“…6,30 In vivo data show that increased bone resorption occurs at an early stage in the development of OA and that blocking bone-resorbing cytokines prevents cartilage damage; 2,31 these data infer the bone factors may play an important role in cartilage behaviour. We found that secreted factors from osteoclasts modulated the gelatinase activity in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…6,30 In vivo data show that increased bone resorption occurs at an early stage in the development of OA and that blocking bone-resorbing cytokines prevents cartilage damage; 2,31 these data infer the bone factors may play an important role in cartilage behaviour. We found that secreted factors from osteoclasts modulated the gelatinase activity in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…There have been no prior studies on the uptake of exosomes by DPSCs or on the effects of pulp-specific exosomes on the odontogenic differentiation of DPSCs and HMSCs. DPSCs are mesenchymal stem cells derived from the neural crest and possess multi-lineage differentiation potential [5053]. On the other hand HMSCs are marrow derived stromal cells also capable of multi-lineage differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate what kind of stem cell markers are expressed in the LRCs in this study using FACS in the future would guide us to new perspectives in stem cell biology, because it is more difficult and even impossible to identify stem cells in the tissue. Furthermore, green fluorescent protein transgenic mice could be available for the analysis of the relationship between dense LRCs and DPSCs, because DPSCs expressing endogenous GFP maintain their ability to differentiate (Grottkau et al 2010).…”
Section: Mapping Of Lrcs In the Growing Toothmentioning
confidence: 99%